The extent to which training centers are committed to the standards of Technical and Vocational Training Corporation (TVTC) from the viewpoint of training supervisors in the Kingdom of Saudi Arabia - Al Shehri, Ali Mohammed Al-Kedwan (Journal of Economic, Administrative and Legal Sciences, 2021)
The current study aimed to identify the extent to which training centers are committed to the standards of Technical and Vocational Training Corporation (TVTC) from the viewpoint of training supervisors at Technical and Vocational Training Corporation (TVTC) in the Kingdom of Saudi Arabia. The study used the descriptive analytical approach, and the questionnaire was used as a tool to collect information. The study population included all training supervisors at Technical and Vocational Training Corporation (TVTC) in the Kingdom of Saudi Arabia whose number is (175) supervisors. The comprehensive survey method was used in the sample. The conclusions of the study revealed that there is a high level of commitment to the training standards determined by at Technical and Vocational Training Corporation (TVTC) at training centers, and it was found that there are some obstacles and difficulties that prevent achieving technical and vocational training standards in training centers in the Kingdom of Saudi Arabia. The study recommended the necessity to alleviate some of the legislations and laws that hinder the work of training centers in the Kingdom of Saudi Arabia. It also recommended that training centers have to rely on management and leadership for the optimal investment of human resources (HR) by motivating and encouraging them and identify the necessary needs for them to raise the level of their performance.